Peranan komite nasional pemuda Indonesia (KNPI) dalam pembangunan politik: studi kasus di Jawa Barat = The Role of The National Committee of Indonesian - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
This research tries to explain the role of interest group, as one of the component of political system in Indonesia. The purpose of this study is to describe and to analyze the role of The National Committee of National Youth (KNPI) n Indonesia in political development. This study took place in West Java. This research applies the descriptive analytical method. The primary data collection has been carried out technically through observations, and depth interviews with prominent young leaders: such as leaders of youth organizations, members of regional regional councils of the KNPI throughout West Java, former young leaders of West Java, some university students in Bandung and the like. Secondary data collection was carried out through extensive documentary data analysis. The result of this research indicates that the KNPI of West Java has contributed a significant role of the political development such as proposed by Samuel-P. Huntington. Nevertheless, since Indonesian political system is under the bureaucratic polity and the hegemonic party system, the KNPI has not been able in fulfilling its important role as expected. The KNPI participated in the policy process through the legislature but its role in political articulation, political aggregation, political socialization, political recruitment, and political communication has been performed independently.